Role of induced sputum with hypertonic saline in the early diagnosis of no / inadequate sputum or sputum smear negative suspected cases of pulmonary tuberculosis - Kapur, Mayank; Luhadia, Atul; Luhadia, Shanti Kumar (International Journal of Research in Medical Sciences, 2017)
Background: Pulmonary Tuberculosis is one of the common infections in the world, especially in developing countries like India and is a leading cause of morbidity and mortality worldwide. Therefore, early diagnosis and microbiological confirmation of pulmonary TB is important. This study was done to assess the role of induced sputum with hypertonic saline in suspected pulmonary TB patients who produce no or inadequate sputum or who are sputum for AFB smear negative. Methods: 100 patients with clinical and radiological evidence of pulmonary TB with no or inadequate sputum or who are smear negative with spontaneous sputum were included in the study. Sputum was induced with 5ml of 3% hypertonic saline delivered through nebulizer and then was sent for Ziehl Neelsen staining examination. Results: 96 patients could produce adequate sputum after sputum induction. In 47 patients, sputum for AFB smear was found positive after induction. Conclusions: Sputum induction is a safe, cheap and non-invasive procedure and offers an alternative or additional approach in the diagnosis of sputum smear-negative suspected pulmonary tuberculosis patients and would enhance sensitivity for the diagnosis of tuberculosis.